2009
DOI: 10.1158/0008-5472.can-09-0820
|View full text |Cite
|
Sign up to set email alerts
|

3-Phosphoinositide–Dependent Kinase 1 Potentiates Upstream Lesions on the Phosphatidylinositol 3-Kinase Pathway in Breast Carcinoma

Abstract: Lesions of ERBB2, PTEN, and PIK3CA activate the phosphatidylinositol 3-kinase (PI3K) pathway during cancer development by increasing levels of phosphatidylinositol-3,4,5-triphosphate (PIP 3 ). 3-Phosphoinositide-dependent kinase 1 (PDK1) is the first node of the PI3K signal output and is required for activation of AKT. PIP 3 recruits PDK1 and AKT to the cell membrane through interactions with their pleckstrin homology domains, allowing PDK1 to activate AKT by phosphorylating it at residue threonine-308. We sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
123
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 48 publications
12
123
0
3
Order By: Relevance
“…However, in this study, PIK3CA mutations [41] were found in both drug-sensitive and drug-resistant breast cancer cells ( 56] failed to demonstrate a correlation between the presence of PIK3CA mutations and expression of pAKT, nor did they provide evidence that such mutations shorten survival or elevate chemoresistance in breast tumor patients [55]. Consistently, recent evidence indicates that when PDK1, which is overexpressed in a large proportion of breast cancers [8], is activated by mutant PIK3CA, it phosphorylates SGK3 rather than AKT [56]. Therefore, PIK3CA mutations may at best contribute to drug-refractory AKT signaling and growth resistance, but are definitely not the sole causes for it.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, in this study, PIK3CA mutations [41] were found in both drug-sensitive and drug-resistant breast cancer cells ( 56] failed to demonstrate a correlation between the presence of PIK3CA mutations and expression of pAKT, nor did they provide evidence that such mutations shorten survival or elevate chemoresistance in breast tumor patients [55]. Consistently, recent evidence indicates that when PDK1, which is overexpressed in a large proportion of breast cancers [8], is activated by mutant PIK3CA, it phosphorylates SGK3 rather than AKT [56]. Therefore, PIK3CA mutations may at best contribute to drug-refractory AKT signaling and growth resistance, but are definitely not the sole causes for it.…”
Section: Discussionsupporting
confidence: 60%
“…All ErbB receptors except ErbB3 activate various downstream signaling molecules including the phosphatidylinositol 3-kinase (PI3K) and its downstream mediators AKT and mTOR, and the mitogen-activated protein kinase (MAPK) cascade proteins C-RAF, MEK, and ERK [7,8]. Both, the MAPK-and the PI3K signaling pathway, have been involved in resistance of tumor cells against ErbB-targeting drugs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…34 Recently, the GCK-like kinase (MAP4K3) has been shown to directly phosphorylate PKCy on T538. 35 Although expression of GLK has not been studied in breast cancer, both LCK 36 and 3-phosphoinositide-dependent kinase 1 37 have been reported to be overexpressed, especially in ERÀ compared with ER þ tumours for the tyrosine kinase. (b) MCF7 cells were transiently transfected with 50 ng of the pIRES2 --EGFP vector expressing either wild-type Fra-1 (WT) or mutated Fra-1 in which serines 252 and 265 were replaced by alanine (S/A).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Activating mutations in PIK3CA, which encodes the PI3K catalytic subunit, have been reported in approximately a quarter of breast tumors 3 and copy number gain of this gene has been identified in 1-14% of breast cancers. [4][5][6] Approximately one fifth of breast cancers are described as having loss of phosphatase and tensin homologue deleted on chromosome 10 (PTEN) expression (range 4-48%) [6][7][8][9][10][11][12][13][14][15] and epigenetic silencing of the PTEN gene through promoter hypermethylation has been reported in 34% 16 and 48% 17 of breast cancers. Loss of heterozygosity at the PTEN locus is observed in 40% of invasive breast carcinomas 18,19 but mutations in this gene have only been identified in 2-9% of breast cancers 3,7,[20][21][22] suggesting that PTEN haploinsufficiency may have tumorigenic consequences.…”
mentioning
confidence: 99%